State of Lara ́s, Venezuela foothills land-use and its effect on physical and chemical properties and rhizosphere bacteria - Torres, Duilio; López, Marisol; Contreras, Jorge; Henríquez, Manuel; Acevedo, Ingrid; Agurto, Claudia (Revista Mexicana de Ciencias Agrícolas, 2018)
The effects of different types of land use (TUT) in the Andean region of the State of Lara on the physical and chemical variables and, on the nitrogen-fixing free-living (FNVL) and phosphate solubilizing rhizosphere bacteria (SF). Altered soil samples were collected in different management practices tested: TUT-coffee, TUT-tomato, TUT-maizeinPiedradelTigre,TUT-leekinBuenaVista, TUT-bean and TUT- lettuce in Palmira. The TUT in Piedra del Tigre appear to be affecting the available phosphorus, but not the evaluated physical properties and rhizosphere bacteria. The least affectation is attributed to the poor soil mechanization and little use of organic fertilizers. FNVL and SF colonies were not affected, although FNVL in the TUT-coffee were lower. All the TUT ́s showed high accumulation of organic matter, mainly the TUT coffee, maize and tomatoes; its low levels of phosphorus appear to be associated with the retention of this element in organic form. In the area of Palmira, theTUT-lettucepresentedhighnutrientavailabilityand colony forming units per ml (CFU ml-1) of SF and FNVL in dilutions of 105 and 106 and fewer CFU ml-1 of FNVL in TUT-bean.
Keywords: rhizosphere bacteria; soil management; sustainability